Development Of The English Grammar Tradition Of The New English Period (On The Example Of Non-Finite Forms) - Yu Sokolova, Alina (Opción, 2019)
As you know, the New English period is characterized by the development of scientific interest in the language, the need to describe the language, the development of the language norm. In this regard, a large number of grammars appear. This article presents the results of the analysis of the interpretation of non-finite forms of the English verb in the grammar books of the New English period.